Economic Impacts of Drought on Water Users of uMhlathuze Municipality of South Africa - Buthelezi, Ntandoyenkosi Nokuthula (Journal of human ecology (Delhi), 2020)
The 2015-2016 drought severely affected KwaZulu Natal, one of the Provinces in South Africa, and undercut its economy. Although the drought's economic impacts on the Province are to some degree covered in literature, however, there is lacking any research inquiry into the impacts of the drought on uMhlathuze Municipality, which is an important economic hub in the Province. This paper, therefore, investigates the economic impacts of the 2015-2016 droughts on commercial agriculture and industrial activities in uMhlathuze Local Municipality. Relying on field observation and the use of secondary data, the findings showed that the 2015-2016 drought impacted flows in rivers, lakes' water level, agricultural sector, industrial sector and other sectors, which operations depend on water availability, and reduced the share of the gross domestic product contributed by the Municipality. The study recommends improved water conservation and redistribution strategy that ensures judicious water use and efficient drought preparedness.